PELUANG PEMANFAATAN SAMPAH PLASTIK MENJADI SUMBER ENERGI - Ansar, Muhammad; Dirawan, Gufran Darma (Pascasarjana Universitas Negeri Makassar, 2025)
The problem of plastic waste that has reached a global and national crisis level, with Indonesia as one of the main contributors to marine plastic waste, has encouraged the urgency of finding a comprehensive management solution, where the utilization of plastic waste as an alternative energy source through thermochemical conversion technology such as pyrolysis, gasification, and incineration (PLTSa) within a circular economy framework is the main study of this article. Based on literature studies, it is known that each technology has unique characteristics related to processes, energy products, efficiency, costs, suitability of plastic types, and environmental impacts. Implementation in Indonesia shows the existence of operational PLTSa and the potential for developing other technologies supported by national policies, but requires strengthening incentives, an integrated approach, selecting technology based on local context, strengthening research, developing supporting policies, and increasing capacity and public awareness for sustainable optimization.